2015
DOI: 10.5751/es-07329-200319
|View full text |Cite
|
Sign up to set email alerts
|

Individual- and community-level impacts of volunteer environmental monitoring: a synthesis of peer-reviewed literature

Abstract: ABSTRACT. Citizens have long contributed to scientific research about the environment through volunteer environmental monitoring programs. Their participation has also resulted in outcomes for themselves, their communities, and the environment. This research synthesizes 35 peer-reviewed journal articles that reported such outcomes through 2012. This collection of articles was derived from a pool of 436 peer-reviewed journal articles about participatory environmental monitoring. Reported outcomes for participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 47 publications
(112 reference statements)
1
110
0
2
Order By: Relevance
“…Educational outcomes are the most frequently studied effect of citizen science projects, according to one metaanalysis of the literature (Stepenuck and Green 2015). Most studies, unsurprisingly, show that citizen scientists learn content knowledge about the subject they are studying, although if participants who elect to join a project already have high levels of science education, such gains may not occur (Overdevest, Orr, and Stepenuck 2004).…”
Section: (2) Expanding Scientific Literacy and Environmental Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Educational outcomes are the most frequently studied effect of citizen science projects, according to one metaanalysis of the literature (Stepenuck and Green 2015). Most studies, unsurprisingly, show that citizen scientists learn content knowledge about the subject they are studying, although if participants who elect to join a project already have high levels of science education, such gains may not occur (Overdevest, Orr, and Stepenuck 2004).…”
Section: (2) Expanding Scientific Literacy and Environmental Awarenessmentioning
confidence: 99%
“…Numerous other studies present evidence that participation in citizen science builds "social capital" (Stepenuck and Green 2015;Wagner and Fernandez-Gimenez 2008;Floress, Prokopy, and Allred 2011;Nerbonne and Nelson 2004). Social capital is typically conceptualized as trust, norms of reciprocity, and social networks that enable a community to collectively solve problems.…”
Section: (3) Building Social Capital and Community Leadershipmentioning
confidence: 99%
“…Most have concluded that, with appropriate resourcing and robust protocols, volunteer data agree closely enough with professional data for use in government http://www.ecologyandsociety.org/vol21/iss4/art32/ Involving community members in monitoring increases not only their ability to contribute data, but also their ability to discuss their knowledge with experts (described as "interactional expertise" by Carolan 2006). Community members participating in environmental monitoring also commonly show increased scientific literacy, greater awareness of local ecosystems and wider environmental issues, stronger social networks including relationships with local government, and greater interest in freshwater planning (Bliss et al 2001, Savan et al 2003, Overdevest et al 2004, Pollock and Whitelaw 2005, Stepenuck and Green 2015, Peters et al 2015b. All of these benefits may lead to more effective community engagement with government in freshwater decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Stepenuck and Green (2015) have studied when and how instances of volunteer environmental monitoring leads to impacts on individual and community level. Their article gives a state of the art overview of research on this topic, with an extensive literature analysis and evaluation of advancements in this field.…”
Section: Voluntary Environmental Monitoringmentioning
confidence: 99%
“…She calls for research on questions around the experience and changing values of participants in voluntary (biological) monitoring and the conditions required for empowerment in relation to participatory environmental governance. In our research, coming from a background in participatory planning and GIS, we have not studied the literature on environmental monitoring in-depth as Stepenuck and Green (2015) have, but rather, we have looked at cases in planning practice where we have seen citizens taking initiatives to gather information. We have analyzed to what extent, and how, those citizen-initiated practices have influenced decision-making processes on the level of governance and collective action.…”
Section: Voluntary Environmental Monitoringmentioning
confidence: 99%